PENGARUH DISIPLIN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA DINAS PENDIDIKAN KABUPATEN TANJUNG JABUNG BARAT - Yunan Surono; Nur Ainun (J-MAS (Jurnal Manajemen dan Sains), 2017)
Nur Ainun/B.14022002/2016/ Pengaruh Disiplin Dan Motivasi Kerja Terhadap Kinerja Pegawai Pada Dinas Pendidikan Kabupaten Tanjung Jabung Barat/ Dr. Hj,Tetty Asnawi, MM Pembimbing I/ M. Zahari MS, SE, M.Si, Pembimbing II. Human resources is one of the most important factor, because of the absence of the role of human resources quality, all activities within an agency will not be implemented optimally. An institution that wants to carry out its duties and functions properly, then the management of human resources. The purpose of this study was to examine the influence of discipline, motivation and performance. Effect of discipline, motivation and performance of employees tested either directly or indirectly. This Penenlitian used a sample of 80 employees spread on the District Education Office in Tanjung Jabung Barat.Keyword : Work Discipline, Work Motivation, Employee Performance